Ibadah Haji dan Kontribusinya Terhadap Berbagai Bidang Sosial Masyarakat Di Indonesia (Tahun 1900-1945) - Wibowo, Eka Yudha (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
The implementation of the pilgrimage in the mid-19th century experienced a significant increase. Various purposes and activities they do while in the holy land. For those who have high dedication to the fate of their people, they prefer to live there for several years and study various fields of religion and other sciences. For those who go straight home after performing the pilgrimage, of course it also has a psychological impact on themselves and gives a better understanding of Islam for others. Those who studied in the holy land in the 19th century generally had a purpose other than to be able to obtain sufficient knowledge there was also to seek support from various parties to expel invaders in Indonesia through the formation of Islamic organizations. This study is examined by looking at the contribution of the Hajj in various social fields that occur after performing the worship for the people in Indonesia.